The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.bonr.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene particles inserted over calvarium induce cancellous bone loss in femur in female mice

Abstract: Focal bone resorption (osteolysis) induced by wear particles contributes to long-term orthopedic joint failure. However, the impact of focal osteolysis on remote skeletal sites has received less attention. The goal of this study was to determine the effects of polyethylene particles placed over calvaria on representative axial and appendicular skeletal sites in female mice. Because recent work has identified housing temperature as an important biological variable in mice, response to particle treatment was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Therefore, the similarity of response to particle-induced osteolysis in ob/ob mice housed at room and thermoneutral temperature argues against higher sympathetic tone in WT mice as being an important factor in particle-induced osteolysis. We have confirmed this conclusion by performing additional temperature studies in which osteolysis did not differ between WT mice housed at 22 °C or 32 °C 56 .…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, the similarity of response to particle-induced osteolysis in ob/ob mice housed at room and thermoneutral temperature argues against higher sympathetic tone in WT mice as being an important factor in particle-induced osteolysis. We have confirmed this conclusion by performing additional temperature studies in which osteolysis did not differ between WT mice housed at 22 °C or 32 °C 56 .…”
Section: Discussionsupporting
confidence: 67%
“…Female mice housed at thermoneutral have higher BMAT and cancellous bone mass than female mice housed at room temperature but antagonizing accrual of BMAT by treatment with the nonspecific β-adrenergic receptor antagonist propranolol had minimal effect on bone mass, microarchitecture and turnover ( 31 ). Additionally, in spite of differences in BMAT, inflammation-induced bone loss was similar in distal femur metaphysis of female mice housed at room temperature and at thermoneutral ( 46 ).…”
Section: Discussionmentioning
confidence: 96%
“…Thermoneutral housing alters many, but not all, metabolic responses ( 67 70 ). Regarding bone, compared to room temperature, thermoneutral housing prevents premature cancellous bone loss, attenuates risperidone-induced trabecular bone loss, has modest effects on cortical response to mechanical loading, and does not impact polyethylene-particle induced osteolysis ( 46 , 71 , 72 ). We have shown that increasing environmental temperature from room temperature to thermoneutral impacts gene expression in WAT and bone ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model, it has been seen that autophagy-mediated osteoblast apoptosis promotes osteolysis in vitro and in vivo (2,154,156). Osteoblast exposure to wear particles impairs mineralization by reducing the gene of ALP, runx 2, osterix, and late osteogenic markers such as osteocalcin (157) and impairs the capacity to synthesize type I collagen, the particle-induced inhibition of osteogenic differentiation by WNT/b-catenin and BMP/Smad signaling pathways, and the imbalance between osteoblastic MMPs and tissue inhibitors of metalloproteinases (TIMPs) (158). This imbalance could result in limited osseointegration and consequently the loosening of the implant (158).…”
Section: Osteoblasts: a Contributor To Bone Resorptionmentioning
confidence: 99%